Inclusive Housing Environments for People With Intellectual Disabilities: Systematic Review of Characteristics and Influencing Factors - Quesada‐Cubo, Mª. Ángeles; Iáñez‐Domínguez, Antonio; Díaz‐Jiménez, Rosa Mª. (Journal of applied research in intellectual disabilities, 2025)
Although efforts have been made to adapt housing to the needs of people with intellectual disabilities, environmental factors remain fragmented and poorly systematised. This study identifies and organises these factors to inform more inclusive and responsive housing design. A systematic review following PRISMA guidelines was conducted across six databases, selecting 73 studies based on predefined criteria. An inductive matrix was developed to group the identified factors into five interrelated environmental dimensions: physical, social, natural, supportive and symbolic. This framework highlights the diversity and depth of elements relevant to housing design, moving beyond accessibility to adopt a biopsychosocial perspective that promotes well-being and health. The methodological, geographical and temporal characteristics of the selected articles were also assessed. This study proposes a pioneering and practical reference framework for designing and evaluating housing for people with intellectual disabilities. It also outlines directions for future research to support inclusive, evidence-based policies and practices.